Mercury accumulation in the sediment of the Western Mediterranean abyssal plain: A reliable archive of the late Holocene. (15th September 2021) - Cossa, D.; Mucci, A; Guédron, S.; Coquery, M.; Radakovitch, O.; Escoube, R.; Campillo, S.; Heussner, S.
Abstract: Temporal reconstruction of Hg deposition from sediment archives is relatively straightforward in organic-rich or high sedimentation rate environments, such as lakes and ocean margins. To retrieve long-term records at regional or global scales, deep-sea sediments are more appropriate, but such records are scarce and their reliability has been questioned because of possible post-depositional Hg diagenetic remobilization. Here, we investigated the accumulation of Hg in the Balearic Abyssal Plain (2850 m deep) of the Western Mediterranean through a comprehensive characterization of the chemical and isotopic composition (organic carbon, nitrogen, sulfur, major and redox-sensitive elements) of sediment trap material and sediment cores. The analysis of material collected in the sediment traps, deployed at 250, 1440, and 2820 m, indicates that Hg is (i) partially re-emitted to the atmosphere and mobilized in the twilight zone and that (ii) the Hg downward flux depends on the primary production in surface waters, suggesting that organic matter (OM) acts as the main Hg-carrier phase. As the Hg concentrations of material collected in the traps vary little with depth but the Hg:Corg ratio of the settling particulate matter decreases with depth, Hg must be re-adsorbed onto the more refractory fraction of the settling OM. Results of selective chemical extractions of the sediment indicate that Hg is very weakly coupled to the iron cycle but strongly associated with sulfur, supporting the assumption that its vertical distribution was only weakly altered by diagenetic remobilization. In addition, the distributions of S and δ 34 S in the sedimentary column exclude the possibility that local volcanism impacted on Hg enrichment of the sediments. Accordingly, a reconstruction of Hg accumulation rates (Hg-AR) during the Late Holocene is readily achieved. Biological mixing and smoothing of the sediment record, as revealed by the distribution of radionuclides in surface sediments, was considered in the interpretation of the Hg-AR record. The first anthropogenic Hg signal recorded in the studied cores corresponds to the Iron Age and the Roman Empire period, as Hg-ARs rose from the baseline (0.7 ± 0.2 µg m −2 yr −1 ) to an average value of 2.2 ± 0.5 µg m −2 yr −1 . The Hg-ARs return to baseline values at the decline of the Roman Empire, display a small increase during the Medieval Period (1.5 ± 0.5 µg m −2 yr −1 ), increase abruptly at the onset of the Industrial Era, leading to a ~ 10-fold increase in Hg deposition in the last 120 years (8.9 ± 1.4 µg m −2 yr −1 ), and retreat progressively over the past 50 years.